Compliance and the role of supervision related to the use of personal protective equipment (PPE) in laundry officers: Personal Protective Equipment (Ppe) - Khoirotun Najihah; Aida Sulisna; Nur Amalia (Institute of Computer Science (IOCS), 2023)
The hospital is one of the workplaces with various threats of danger that can have health impacts,One of the high-risk hospital workers is laundry workers because they are not equipped with special skills to become laundry and someof them do not use Personal Protective Equipment (PPE) to protect workers from various threats of danger. This study aimed to know how the compliance and monitoring of using Personal Protective Equipment (PPE) for Laundry Officers at Sultan Iskandar Muda Hospital, Nagan Raya Regency. Method: This is a qualitative descriptive research method which aims to describe, summarize various conditions, situations, or various phenomena of social reality that exist in the community. The research informants was 11 people. Data analysis was done by using data reduction, data presentation and data verification. Results: The results showed that there was a compliance and a monitoring. That influenced of using the Personal Protective Equipment For laundry workers. Conclusion: The conclusion of the study shows that there is an effect of compliance and supervision on the use of Personal Protective Equipment (PPE). It is suggested to the Hospital, to provide training on the use of PPE for laundry workers.